2016
DOI: 10.1364/ol.41.004899
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of predesigned optical materials in nematic codispersions of plasmonic nanorods

Abstract: Optical metamaterials and other nanostructured metal-dielectric composites hold great potential for designing and practically realizing novel types of light-matter interactions. Here we develop an approach to fabricate composites with tunable pre-engineered properties via self-assembly of anisotropic nanoparticles codispersed in a nematic liquid crystal host. Orientations of plasmonic nanorods of varying aspect ratios are controlled to align parallel or perpendicular to the nematic director and retain this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…By changing the geometry of nanoparticles and different kinds of LC materials (nematic and cholesteric LCs), the authors also showed that the switching time of the composite could be tuned from milliseconds to seconds and even the polarization of the transmitted light could be manipulated according to the application demands. Another solution, which was proposed by the same group, was co-dispersing different anisotropic nanoparticles in LCs [269]. The authors used gold nanorods with varying aspect ratios in a nematic LC host (5CB).…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…By changing the geometry of nanoparticles and different kinds of LC materials (nematic and cholesteric LCs), the authors also showed that the switching time of the composite could be tuned from milliseconds to seconds and even the polarization of the transmitted light could be manipulated according to the application demands. Another solution, which was proposed by the same group, was co-dispersing different anisotropic nanoparticles in LCs [269]. The authors used gold nanorods with varying aspect ratios in a nematic LC host (5CB).…”
Section: Photonic Applicationsmentioning
confidence: 99%
“…Elastic trapping of nanoparticles in LC line defect. We used 40 x 65 nm GNRs (Figure 1), which were synthesized by following the seed-mediated method described in detail elsewhere [25][26][27] (See materials and methods). We also utilized commercially available CdSe/ZnS core-shell QDs (Ocean nanotech) shown in Figure 1e, which were selected for their emission peak at 620 nm.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)-(c)). GNRs with the longitudinal SPR peak at 815 nm were surface-functionalized with thiol-terminated methoxy-poly(ethylene glycol) (mPEG-SH 5kDa, JemKem Technology) [10]. For some GNRs, porous silica shells were grown around the nanoparticles ( Fig.…”
Section: Methods and Designmentioning
confidence: 99%